How social motivation enhances economic activity and incentives in the Google Answers knowledge sharing market. (27th February 2007) - Rafaeli, Sheizaf; Raban, Daphne R.; Ravid, Gilad
What are the antecedents, inhibitors and catalysts to providing information and participating in mixed fee-based and free online contexts? We describe the behaviour of about 500 'Researchers' in the Google Answers (GA) online service and over 70, 000 questions posed on this system over a 29 month period. GA is a fee-based environment. Answers provided on it are 'worth' over 20 (including tips) on average. However, labour economics of response to price and tip alone do not fully account for the online information provision market. Non-monetary incentives, such as feedback in the form of comments predict and explain some of the variance in participation. Descriptive and correlational findings presented here are based on many thousands of answers. We thus corroborate some of the hybrid theories of information provision behaviour presented to date mostly in laboratory settings. The participation of experts in GA is associated with a hybrid of material (economic) and social motivators.